Solitary lumbar osteochondroma presenting with spinal cord compression. (31st July 2013) - Natale, Massimo; Rotondo, Michele; D'Avanzo, Raffaele; Scuotto, Assunta
Abstract : We report a case of a middle-aged woman with a solitary osteochondroma of the L2 right lamina with intraspinal extension and spinal cord compression. The case is unusual in terms of localisation and age at clinical presentation. In fact, spinal osteochondromas as solitary lesions—especially when affecting the lumbar segment—are rare tumours of a maturing adolescent skeleton, infrequently affecting the neurological structures, because most of the lesions grow out of the spinal canal. Although unusual, they should be considered in the differential diagnosis. Prompt and accurate radiological investigations are important in planning appropriate management. Surgical total excision is the best treatment modality to remove spinal cord and/or nerve root compression, and to avoid the risk of recurrence or malignant transformation.